2019
DOI: 10.1017/s071498081900045x
|View full text |Cite|
|
Sign up to set email alerts
|

Burden on Caregivers of Adults with Multiple Chronic Conditions: Intersectionality of Age, Gender, Education level, Employment Status, and Impact on Social Life

Abstract: RÉSUMÉ L’analyse de l’intersectionnalité est l’étude des identités sociales qui se chevauchent ou se recoupent. L’intersection d’identités sociales peut avoir une incidence sur la perception du fardeau assumé chez les aidants naturels prenant soin de personnes âgées atteintes de maladies chroniques multiples (MCM). Le but de l’étude était d’explorer l’interaction des facteurs sociaux sur le fardeau associé aux soins apportés aux personnes âgées atteintes de MCM. Au total, 194 aidants de personnes âgées atte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Our study was not focused on the needs of carers specifically, but our small sample of carers revealed their own challenges with administering insulin and hypoglycaemia fears. There is a large body of literature that points to the burden of caring for people with long-term conditions such as diabetes [ 54 , 55 ], yet there is still some way to go in terms of making carers feel more confident, empowered and skilled [ 56 ]. There is clearly a need for developing education designed specifically for the carers of older people to enhance their ability to deliver effective diabetes care to their relatives.…”
Section: Discussionmentioning
confidence: 99%
“…Our study was not focused on the needs of carers specifically, but our small sample of carers revealed their own challenges with administering insulin and hypoglycaemia fears. There is a large body of literature that points to the burden of caring for people with long-term conditions such as diabetes [ 54 , 55 ], yet there is still some way to go in terms of making carers feel more confident, empowered and skilled [ 56 ]. There is clearly a need for developing education designed specifically for the carers of older people to enhance their ability to deliver effective diabetes care to their relatives.…”
Section: Discussionmentioning
confidence: 99%
“…Females have historically been depended on in the home for healthcare delivery, both in acute and chronic disease states (Morgan et al, 2016). As a result, females report more caregiver burden than males (Ghosh et al, 2020; Yu et al, 2019), especially in low- and middle-income settings (Akgun-Citak et al, 2020). The healthcare needs of older adults with more than one disease, such as diabetes mellitus and hypertension, result in an increased financial burden for them, their informal caregivers, and the healthcare system as a whole (Ferris et al, 2018; He et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research related to caregivers of people at end of life and living with life‐limiting conditions and mental illness identified that the influence of caregiver sex on the risk of negative outcomes and consequences is often overlooked and misunderstood (Gardiner et al., 2020; Ghosh et al., 2020; Pinquart & Sorensen, 2006; Sharma et al., 2016). This study demonstrates that there is meaning and knowledge to be found by disaggregating caregiver data by sex.…”
Section: Discussionmentioning
confidence: 99%
“…Fromme et al (2005) suggested that women report more strain because women are more likely to share their emotions. Indeed, females do tend to have better social support (Wong & Hsieh, 2019), and poor social networks are linked to an increased risk of caregiver burden (Ghosh et al, 2020). Nevertheless, research suggests that not only are women more likely to care for more hours than men (Pinquart & Sorensen, 2006), caring for people with more complex needs.…”
Section: The 'Crisis Of Care'mentioning
confidence: 99%